Stereoselective Reactions of ortho-Quinone Methide and ortho-Quinone Methide Imines and Their Utility in Natural Product Synthesis - Nielsen, Christian D.-T.; Abas, Hossay; Spivey, Alan C. (Synthesis, 2018)
Herein presented is a review of the reactivity and synthetic utility of ortho-quinone methides and ortho-quinone methide imines. These versatile intermediates have received significant attention in the literature and new methods for their preparation and reaction as well as recent applications in total synthesis are discussed.1 Introduction2 Conjugate Addition Reactions3 Concerted Cycloaddition Reactions4 Stepwise Addition Reactions5 Applications in Total Synthesis6 Conclusion
Keywords: ortho-quinone methide; ortho-quinone methide imine; total synthesis; review